Philosophy of Islamic shari'ah and its contribution to the science of contemporary law 2026-02-15T21:03:27+03:00 DEBUG: VuFind\ILS\Driver\Folio: Token taken from global cache: eyJhbGciOiJIUzI1NiJ9.eyJzdWIiO... - Kharufah, Ala al-Din (Eminent Scholars's Lecture Series ; ;, 2000)

(untitled)
Islamic law; philosophy; law; 20th century